2013
DOI: 10.1007/s00005-012-0212-z
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte-Colony Stimulating Factor as Treatment Option in Patients with Recurrent Miscarriage

Abstract: In 1-5 % of patients during childbearing years recurrent miscarriages (RM) occur. There are established risk factors like anatomical, endocrine and hemostatic disorders as well as immunological changes in the maternal immune system. Nevertheless, further elucidation of the pathogenesis remains a matter of debate. In addition, there are no standardized immunological treatment strategies. Recent studies indicate possible effects of tumor necrosis factor a blocker and granulocyte-colony stimulating factor (G-CSF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 32 publications
0
42
1
2
Order By: Relevance
“…G-CSF enhances the cyclic adenosine monophosphate-mediated decidualization of human endometrial stromal cells in an autocrine or paracrine fashion [22]. It has been reported that G-CSF, when injected subcutaneously, acts on embryo implantation by modulating the immune reaction and affecting the function of macrophages in the decidua [2324]. Culture of luteal endometrial tissue together with recombinant G-CSF was found to stimulate the expression of several genes that play a crucial role in embryo implantation (i.e., endometrial vascular remodeling, immune modulation, and/or cellular adhesion pathways) [25].…”
Section: Discussionmentioning
confidence: 99%
“…G-CSF enhances the cyclic adenosine monophosphate-mediated decidualization of human endometrial stromal cells in an autocrine or paracrine fashion [22]. It has been reported that G-CSF, when injected subcutaneously, acts on embryo implantation by modulating the immune reaction and affecting the function of macrophages in the decidua [2324]. Culture of luteal endometrial tissue together with recombinant G-CSF was found to stimulate the expression of several genes that play a crucial role in embryo implantation (i.e., endometrial vascular remodeling, immune modulation, and/or cellular adhesion pathways) [25].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had showed that G-CSF can improve recurrent pregnancy losses by increasing the infl ammation process and subsequently endometrial receptivity [8][9][10][11]. reported that the pregnancy chances and endometrial thickness was improved after G-CSF infusion [13].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies had shown that systemic administration of G-CSF in patients with recurrent spontaneous pregnancy losses and repetitive implantation failures improves pregnancy outcomes [8][9][10]. Also, G-CSF transvaginal infusion successfully were utilized in women with low endometrial 3(1): 011-014.…”
Section: Introductionmentioning
confidence: 99%
“…Eine Subgruppe wurde nicht medikamentös behandelt, die zweite erhielt relevante Medikamente wie LMWH, Acetylcholinsäure, Folsäure, Kortison oder Doxyzyklin. Es zeigten sich signifikante Unterschiede zwischen den Subgruppen: Die Schwangerschaftsrate betrug [21] F 47% nach subkutaner G-CSFApplikation, F 25% bei RSA-Patientinnen ohne Medikation, F 27% bei alternativer Medikation.…”
Section: G-csfunclassified
“…In keiner der klinischen Studien zeigte sich eine erhöhte Fehlbildungsrate oder schwere Nebenwirkungen der in utero exponierten Feten [21,23,30]. Es traten lediglich lokale Irritationen im Bereich der Injektionsstelle, Fieber, Leukozytose sowie unspezifische Beschwerden wie Übelkeit und Erbrechen auf [2].…”
Section: G-csfunclassified